Variability of external load measures during soccer match play: Influence of player fitness or pacing? - Rabbani, A.; Ermidis, G.; Clemente, M. F.; Twist, C. (International Journal of Sports Physiology and Performance, 2024)
Purpose: The aims of this study were to examine the variability of selected external load metrics within 15-minute intervals during soccer match play and examine their relationship with players` high-intensity intermittent fitness.